PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP MINAT BELI SEPATU ANDO (STUDI KASUS DI KOTA BEKASI 2020) - Netti Natarida Marpaung (Sekolah Tinggi Ilmu Ekonomi Tribuana, 2020)
The purpose of this research was to determine the effect and relationship of variable Brand Image and Product Quality partially and simultaneously on the Interest in Buying Ando Shoes products of PT. Halim Jaya Sakti in Sidoarjo. The method used is to use quantitative data by distributing questionnaires as many as 95 respondents. This research data uses primary data. Sampling analysis tools used are validity test, reliability test, correlation test, classic assumption test, simple linear regression test, t test (partial), F test (simultaneous), and coefficient of determination test using SPSS software version 21.0. Based on the results of this study indicate that the variable Brand Image is quite influential and related which shows a positive and significant direction to the Purchase Interest of Ando Shoes products at Pt. Halim Jaya Sakti in Sidoarjo. Proven in the t test, the Brand Image variable t value> t table is (96.777> 1.66140) and Product Quality variable t value> t table is (108.432> 1.66140) so the correlation test calculation is more significance value smaller than the 0.05 significant level that is equal to 0,000 <0.05.